[192-(45:15)4 ]:3
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) [192 - (45 : 15) ^4 ] = [192 - (3)^4]
= [192 - 81]
= 111
a) [192 - ( 45 : 15)4 ]
= 192 - 34
= 192 - 81
= 110
b) [ (192 - 45 : 15) : 3)2 ]
= [ (192 - 45 : 15) : 3)2 ]
= [ (192 - 3) : 3)2
= (189 : 3)2
= 632
= 3969
\(\left[\left(192-45:15\right):3\right]^2=\left[\left(192-3\right):3\right]^2=\left[189:3\right]^2=3969\)
a) 32-6.(8-23)+18
= 32 - 6 . (8 - 8) +18
=32 - 0 +18
= 50
b) (3.5-9)3.(1+2.3)2+42
= (15-9 )3. (1+6)2 + 4 2
= 63 . 7 2 + 42
= 216 x 49 + 16
= 10584 + 16
=10600
c) 9234:[3.3.(1+83)]
= 9234 : [ 3.3.93]
= 9234 : [ 3.3 . 729]
= 9234 :6561
= 1,407407407
d) 76- {2.[2.52-(31-2.3)]}+3.25
= 76 - { 2. [ 2.52 - ( 31 - 6)]} + 3.25
= 76 - { 2 . [ 2. 52 - 25 ]} + 3 .25
= 76 - { 2 . [2. 25 - 25]} + 3.25
= 76 - { 2.[ 50 - 25 ]} + 3.25
= 76 - { 2. 25} + 3 . 25
= 76 - 50 + 3. 25
= 76 - 50 + 75
= 101
2: \(=234+29-80+52^3=140791\)
3: \(=45\cdot\left(3250-225\right)=45\cdot3025=136125\)
4: \(=\left[\left(192-3\right):3\right]^2=63^2=3969\)
\(\left[192-\left(45:15\right)^4\right]:3\)
\(=\left(192-3^4\right):3\)
\(=192:3-3^4:3\)
\(=64-3^3\)
\(=64-27\)
\(=37\)
cam on nha